(untitled) (Itinera, 2015)
In this article I focus on the notion of “reflective thinking” and on its theoretical and practical relevance. What I endeavour to achieve is that those dialogic practices employing “reflective thinking” succeed in showing that rationality (or system) and improvisation (or freedom) are mutually and inseparably intertwined. The case study of the “Philosophy for Children” (P4C) curriculum developed at the beginning of the 1970s by Matthew Lipman and other researchers provides evidence in order to achieve such result.